INTRODUCTION OF A CLINICAL CASE OF COVID-19 SEVERE LUNG INJURY, TREATED BY CORTICOID - Nguyen Quang Huy; Pham Xuan Quang; Nguyen Van Nam; Pham Thai Dung; Nguyen Trung Kien; Vu Minh Duong (Tạp chí Y học Quân sự, 2022)
COVID-19 epidemic appeared at the end of 2019 and it became a global pandemic. That disease was caused by the SARS-CoV-2 virus. There are 20% COVID-19 patients that were hospitalized and 5% lung injury had respiratory failure. Lung injuries that appeared IIA stage were treated by corticoid to significantly improve clinical and subclinical criteria. A severe COVID-19 patient had severe pneumonia (respiratory rate 30 b/m, SpO2 82% with room air, PaO2 67 mmHg, P/F 319, X-ray bilateral diffused consolidated injuries), treated methylprednisolone 1.5 mg/kg/day combined with antibiotics, anticoagulant… The patient gradually recovered, improved clinical criteria, decreased lung injuries on X-ray, discharged after 14 days.